Influence of pH on colour and iron content of peptide fractions obtained from bovine Hb concentrate hydrolysates - Cian, Raúl Esteban (2012)
The effect of pH on colour and iron content (Fe) of peptide fractions obtained from bovine haemoglobin concentrate (BHC) hydrolysates was studied. Four hydrolysates were obtained using three enzymes: Protex- 6-L (P), Fungal?Protease?Concetrate (FC) and Flavourzyme (F). BHC and its hydrolysates (P, FC, P + F, FC + F) were fractioned at pH 4.5, 7.0 and 9.5. Solubility and Fe from different fractions were measured. Correlations between CIELAB colour parameters and Fe from different fractions were analysed. The colour from different fractions varied from red to yellow (a* and b* positives). Lightness values (L*) ranged from twenty-four to seventy. FC4.5 and FC + F4.5 fractions were the clearest and yellow (higher L*, b*, h), while BHC9.5 and P + F9.5 fractions had the lowest values of L*, b* and h. There was an inverse linear relationship between b* and L* parameters and Fe from fractions. This relationship could be associated with the pH of extraction. As pH increases Fe significantly increases and lower b* and L* values were obtained.